2021
DOI: 10.1038/s41419-021-03454-9
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarsenic hexoxide enhances generation of mitochondrial ROS to promote pyroptosis by inducing the activation of caspase-3/GSDME in triple-negative breast cancer cells

Abstract: Although tetraarsenic hexoxide is known to exert an anti-tumor effect by inducing apoptosis in various cancer cells, its effect on other forms of regulated cell death remains unclear. Here, we show that tetraarsenic hexoxide induces the pyroptotic cell death through activation of mitochondrial reactive oxygen species (ROS)-mediated caspase-3/gasdermin E (GSDME) pathway, thereby suppressing tumor growth and metastasis of triple-negative breast cancer (TNBC) cells. Interestingly, tetraarsenic hexoxide-treated TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 33 publications
0
62
0
Order By: Relevance
“…The N domains of the gasdermin family with the exception of DFNB59 are capable of inducing pyroptosis (3,5). In particular, GSDME is cleaved by caspase-3 (Casp3) and switches apoptosis to pyroptosis in several cancers, which is associated with the side effects of chemotherapy and antitumor immunity (6) in breast cancer (7), lung cancer (8), gastric cancer (9) and colorectal cancer (10). Growing evidence suggests that numerous chemotherapeutic drugs, such as cisplatin and etoposide (6), may activate pyroptosis via canonical or noncanonical inflammasome pathways, including TLR and MAPK pathways (11), inhibit cancer progression Long non-coding RNA nuclear paraspeckle assembly transcript 1 regulates ionizing radiation-induced pyroptosis via microRNA-448/gasdermin E in colorectal cancer cells and overcome apoptosis resistance, which are major causes of cancer resistance (12).…”
Section: Introductionmentioning
confidence: 99%
“…The N domains of the gasdermin family with the exception of DFNB59 are capable of inducing pyroptosis (3,5). In particular, GSDME is cleaved by caspase-3 (Casp3) and switches apoptosis to pyroptosis in several cancers, which is associated with the side effects of chemotherapy and antitumor immunity (6) in breast cancer (7), lung cancer (8), gastric cancer (9) and colorectal cancer (10). Growing evidence suggests that numerous chemotherapeutic drugs, such as cisplatin and etoposide (6), may activate pyroptosis via canonical or noncanonical inflammasome pathways, including TLR and MAPK pathways (11), inhibit cancer progression Long non-coding RNA nuclear paraspeckle assembly transcript 1 regulates ionizing radiation-induced pyroptosis via microRNA-448/gasdermin E in colorectal cancer cells and overcome apoptosis resistance, which are major causes of cancer resistance (12).…”
Section: Introductionmentioning
confidence: 99%
“…At moderate concentrations, ROS have been implicated in tumor initiation and progression, malignant conversion, and resistance to chemotherapy. The higher concentrations of ROS result in damage cellular biomolecules and cause gene mutations, thus promoting canceration of normal cells or inducing cancer cell apoptosis, necrosis, autophagy, ferroptosis, and pyroptosis [ 48 , 86 ] ( Figure 5 ). Therefore, the roles of ROS are complicated, and ROS operate as a diversified biochemical entity in cancer progression.…”
Section: Ros Paradox and Contradictory Strategies Based On Ros For Cancer Treatmentmentioning
confidence: 99%
“…Since GSDMA and GSDME exert critical tumour‐suppressive effects on tumorigenesis, upregulation of GSDMA/GSDME and induction of GSDMA/GSDME‐related pyroptosis might be a promising therapeutic target for the treatment of cancer. Chemotherapeutics, such as doxorubicin, lobaplatin, cisplatin and tetraarsenic hexoxide, can suppress the growth of neuroblastoma, melanoma, colon cancer cells and breast cancer by inducing GSDME‐mediated pyroptosis 85–88 . Recently, Zhang et al 33 showed that intratumoral injection of DM‐αKG can notably repress tumour growth and metastasis through caspase‐8‐GSDMC‐mediated pyroptosis.…”
Section: Pyroptosis In Noninfectious Diseasesmentioning
confidence: 99%
“…Chemotherapeutics, such as doxorubicin, lobaplatin, cisplatin and tetraarsenic hexoxide, can suppress the growth of neuroblastoma, melanoma, colon cancer cells and breast cancer by inducing GSDME‐mediated pyroptosis. 85 , 86 , 87 , 88 Recently, Zhang et al 33 showed that intratumoral injection of DM‐αKG can notably repress tumour growth and metastasis through caspase‐8‐GSDMC‐mediated pyroptosis. Moreover, GSDME/GSDMB‐dependent pyroptosis is implicated in cytotoxic T lymphocytes or chimeric antigen receptor (CAR) T cell‐mediated antitumour immunity.…”
Section: Pyroptosis In Noninfectious Diseasesmentioning
confidence: 99%